TINGKAT KEPUASAN PASIEN TERHADAP MUTU PELAYANAN DI POLIKLINIK GIGI PUSKESMAS SUKAWATI II TAHUN 2015 - I Putu Agus Eka Putra; I Made Budi Artawa; I Komang Mahendra (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2016)
The improvement of people knowledge demanded a satisfying health quality for the consumers. Satisfaction is a happy feeling of person after comparing between the reality and their hope. The purpose of this study was to describe the satisfaction level of the patient through the service at Poliklinik Gigi Puskesmas Sukawati II in 2015. The study is a descriptive using cross sectional and using qualitative method. The population of this study was all the patients who have visited Poliklinik Gigi Puskesmas Sukawati II from 20th – 27th June 2015, the level of satisfaction was measured by the grade for health service. As the result from 45 respondents shows reliability dimension, hope value 559 : reality value 563 and satisfaction value 4 , so it can be categorized as very satisfied. From responsiveness dimension, shows the hope value 411 : reality value 411 and satisfaction value 0, so it can be categorized as satisfied. Assurance dimension shows hope value 555 : reality value 559 and satisfaction value 4, categorized as very satisfied. Empathy dimension, shows hope value 419 : reality value 419 and satisfaction value 0, categorized as satisfied. As the conclusion, all of the five dimensions which is measured from the respondents shows very satisfied with the health service at the reliability, assurance and tangibles dimension. Meanwhile, for the responsiveness and empathy dimension, the respondents feel satisfied. So, as an advice for the Poliklinik Gigi Puskesmas Sukawati II to keep improving their health service for the patients by giving them a better responses